Transient eye closure and ocular preference in patients with intermittent exotropia - Rostami, Masoud; Kiarudi, Mohammad Yaser; Hassanzadeh, Samira; Etezad Razavi, Mohammad; Sharifi, Mahdi; Ziaei, Mohammed (Journal of AAPOS, 2024)
To assess the relationship of sensory and motor ocular dominance to transient eye closure (TEC) under bright light conditions in patients with intermittent exotropia. Forty patients (age range, 7-40 years) with intermittent exotropia were included in this prospective study. Motor and sensory ocular dominance were evaluated using the hole-in-the-card and Worth 4-Dot tests. Presence of any outward eye deviation or TEC was assessed and recorded in all participants under bright light conditions. Based on the fusion control grade of exodeviation, patients were assigned to good, fair, and poor control groups, and the results were compared. A total of 23 patients (58%) showed TEC under bright light: 18 (45%) in the good control group, 14 (35%) in the fair control group, and 8 (20%) in the poor control group. Eighteen patients (56%) with good and fair control showed TEC in the dominant eye. Five (63%) with poor control closed their nondominant eyes, and in all of them, outward eye deviation was observed before TEC. The angle of deviation at far and near and the degree of near stereopsis were not related to presence of TEC (P = 0.70, P = 0.06, and P = 0.34, resp.). In patients with intermittent exotropia who exhibit TEC under bright light, those with good control tend to close the dominant eye, whereas in the majority of patients with poor control, spontaneous deviation occurs and is then followed by TEC of the nondominant eye.